An enterprise risk management framework for managing hazardous operational refinery risks: Case Oman - Al Khusaibi, Thuraiya (2020)
The oil and gas industry is the leading economic contributor in the Sultanate of Oman. It is considered a critical sector that drives the country’s attention to create a comprehensive, reliable, and sustainable performance to create a long-term impact economically. Due to the complexity of the competitive environment in the oil and gas, companies have highlighted the considerable number of risks facing their activities. The environment, health, and well-being of the workforce of oil companies are the most valuable asset that drives the organization productivity in general. The traditional approach of managing risk is not accurate enough to handle the present situation. Better strategies such as enterprise risk management are correctly adjusted to the new modern complex environments. Moreover, integrating step by step ERM approach will enable continual improvement throughout organizations in decision making. Therefore, this study aims to glance at the hazardous operational risks that face the downstream sector in oil and gas companies in Oman, to develop an enterprise risk management framework which will create a shared understanding of the critical risks involved in the industry among all parties, as well as how they can be managed, and mitigated efficiently, effectively, and imperatively productive. The following study will be using both primary and secondary data in the analysis. A questionnaire is designed for the primary method and distributed to 37 workers and management team in Oman’s petroleum refineries. The study identified the critical operational hazardous risks that effect the long-term processing of crude oil in Oman’s petroleum refineries which include, pressure hazard with 33.33 percent and 50 percent assigned as extreme and high risk respectively. Followed by chemical hazard with 27.78 percent and 61.11 percent assigned as extreme and high risk respectively.